РОЛЬ САМООЦІНКИ У ФОРМУВАННІ ГО ТО ДАВНО СТІ СТУДЕНТІВ ДО КРАЄЗНАВЧОЇ (Педагогіка вищої та середньої школи, 2006)
The article considers the author the main point of appreciating component of the readiness for the local lore work of students. It studies a formedap condition of given structural element.